Comparative analysis of the relation between the number of falls annually and a battery of static balance and agility tests in elderly subjects - Javier Sampedro Molinuevo; Agustín Meléndez Ortega; Pedro Ruiz Solano (FEADEF, 2010)
Falls are a serious problem for the elderly because the high rate of mortality and morbidity. The risk factors related to falls are many and it is difficult to isolate the triggering elements. Deficits in balance, problems of sight, decreases of strength in the legs, loss of coordination and changes in propioception are important factors. It is necessary to have simple assessment field tests to detect problems which lead to falls. A group of subjects (n=33), mean age 70,2 + 5,3, and a physical activity profile of at least two days a week, who walked between 35 and 90 minutes as and average, 4 days a week, answered a personal data questionnaire and provided data on falls. The results showed that bipodal standing with open eyes tests were not discriminatory. Significant positive correlations were found between items of static balance test (0,31 < r < 0,71) and the probability limits of 0,001< p < 0,05. It is recommended to include the agility test in assessment.